2021
DOI: 10.3390/v13071284
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Elicited in Response to a Single Cycle Glycoprotein D Deletion Viral Vaccine Candidate Bind C1q and Activate Complement Mediated Neutralization and Cytolysis

Abstract: Herpes simplex virus (HSV) prevention is a global health priority but, despite decades of research, there is no effective vaccine. Prior efforts focused on generating glycoprotein D (gD) neutralizing antibodies, but clinical trial outcomes were disappointing. The deletion of gD yields a single-cycle candidate vaccine (∆gD-2) that elicits high titer polyantigenic non-gD antibodies that exhibit little complement-independent neutralization but mediate antibody-dependent cellular cytotoxicity (ADCC) and phagocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…None of the rAbs inhibited plaque formation by greater than 50% in neutralization assays at concentrations as high as 1 mg/mL even with the addition of rabbit complement, although there was an increase in percentage reduction of viral plaque formation from 10% to 42% inhibition for BMPC-23 (IgG2c) at 1 mg/mL when complement was added ( Figure 3B ). These findings are consistent with the behavior of immune serum obtained from ΔgD-2–vaccinated mice, which exhibited ADCC but not complement-independent neutralizing activity and is distinct from immune sera obtained from rgD-2/AS04–vaccinated mice, which contained complement-independent neutralizing but not FcγRIV-activating antibodies ( 19 , 24 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…None of the rAbs inhibited plaque formation by greater than 50% in neutralization assays at concentrations as high as 1 mg/mL even with the addition of rabbit complement, although there was an increase in percentage reduction of viral plaque formation from 10% to 42% inhibition for BMPC-23 (IgG2c) at 1 mg/mL when complement was added ( Figure 3B ). These findings are consistent with the behavior of immune serum obtained from ΔgD-2–vaccinated mice, which exhibited ADCC but not complement-independent neutralizing activity and is distinct from immune sera obtained from rgD-2/AS04–vaccinated mice, which contained complement-independent neutralizing but not FcγRIV-activating antibodies ( 19 , 24 ).…”
Section: Resultssupporting
confidence: 85%
“…Consistent with that observation, BMPC-23 and the other mAbs we evaluated showed little or no neutralizing activity with only modest increases in neutralization when complement was added to the assay. We previously observed that ΔgD-2 immune serum binds C1q, but this binding is not essential for protection, as passive protection was preserved in C1q-knockout mice ( 24 ); in contrast, passive protection is lost in FcγRIV-knockout mice ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increased susceptibility to manifestation of autoimmunity in females was confirmed in double knockout mice for C1q and H2-Bf/C2 -/- ( 80 ) as well as C1q deficiency in the lupus prone MRL/Mp background ( 71 ). Although this effect is particularly well described for autoimmunity on a lupus prone genetic background, it is still noteworthy that a large number of studies in C1qKO mice included in this review investigated female mice only ( 4 , 11 , 38 , 59 , 60 , 62 , 73 , 76 79 , 87 , 97 , 116 , 125 , 128 , 146 , 149 , 170 ) while others only used male animals ( 26 , 35 37 , 45 , 46 , 50 , 53 , 61 , 63 , 88 , 99 , 110 , 113 , 119 , 141 ) ( Tables 1 – 3 ). Few studies evaluated specifically the differential gender effect ( 12 , 24 , 28 , 55 , 71 , 80 ).…”
Section: Resultsmentioning
confidence: 99%
“…In models of vaccination ( 95 , 97 ) and gene therapy vectors ( 98 , 99 ), there was no major effect of C1q deficiency. Immunoprophylaxis by alloimmunization as performed e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This exciting research may be a major step forward in preventing primary infection. Similarly, live, attenuated herpesviruses can be used to elicit durable, lasting, immune responses to diminish the number and severity of reactivations [ 24 , 25 ]. A fourth paper in this issue [ 26 ] addresses limitations that may be encountered when working with live, attenuated herpesviruses.…”
mentioning
confidence: 99%